Contagious generosity : creating a culture of giving in your church - Willard, Chris, 1964-; Sheppard, Jim, 1954- (Grand Rapids, MI : Zondervan, 2012)
"Chris Willard and Jim Sheppard offer pastors curious about the conversation of Biblical generosity a look inside the practice and habits of generous church leaders in Contagious Generosity--a roadmap pastors can use to accelerate generosity in his or her community of faith"--Publisher description.
pt. 1; Church development -- 1. Culture is key -- 2. Good strategy is better than good intentions -- 3. Generosity is contagious -- pt. 2; Leadership development -- 4. Follow me -- 5. Leverage the weekend experience -- 6. Embrace the ministry of asking -- 7. Disciple high-capacity givers -- pt. 3 Impact -- 8. Measure progress -- 9. You accelerate what you celebrate -- 10. Generosity is the new evangelism -- Conclusion: there is no generosity button.
Keywords: Generosity -- Religious aspects -- Christianity; Christian giving; Christian stewardship